2019
DOI: 10.3389/fmicb.2019.01430
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Isolated From a Cat Is Related to Human Adenovirus 1

Abstract: An adenovirus (AdV) has been isolated from the rectal swab of a domestic cat ( Felis catus ) and named feline adenovirus (FeAdV) isolate. It replicates and causes cytopathological effects in many human, feline, other mammalian cell lines that have both Coxsackie-adenovirus-receptor and integrins. Its antigens cross-react with anti-human adenovirus antibodies in immunofluorescence and immunocytochemistry assays. Electron microscopy revealed typical extracellular icosahedral particles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Even more intriguing is the isolation of a HAdV-1-like virus from cats, following a large sample screening of domestic cats using a HAdV-1 hexon antigen and ELISA in the mid-1990s by Ongradi et al [61]. Sequence determination of the feline hexon and fibre genes showed near-identity to the human counterparts [62]. This virus was reported to replicate in both human and monkey cells in vitro [61], which was updated recently (2019) to include a screen of various permissive and non-permissive human and other animal cells, along with additional immunochemical analyses [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more intriguing is the isolation of a HAdV-1-like virus from cats, following a large sample screening of domestic cats using a HAdV-1 hexon antigen and ELISA in the mid-1990s by Ongradi et al [61]. Sequence determination of the feline hexon and fibre genes showed near-identity to the human counterparts [62]. This virus was reported to replicate in both human and monkey cells in vitro [61], which was updated recently (2019) to include a screen of various permissive and non-permissive human and other animal cells, along with additional immunochemical analyses [62].…”
Section: Resultsmentioning
confidence: 99%
“…Additional relevant studies were published following the initial review in November 2018, including the previously cited Dehghan et al study [40], Ongrádi et al study of feline AdV [62], the Zhang et al study of HAdV-E4 circulating in Hong Kong [59].…”
Section: Discussionmentioning
confidence: 99%
“…Should subsequent amphizoonosis occur, that is, from nonhuman host species and back to humans, potential recombinant AdVs may result in novel, emergent human pathogens. Recent reports indicate that bat and cat harbour at least one AdV each that have gene sequences with significant sequence similarities to their HAdV counterparts (Ongradi, 1999;Phan et al, 2006;Baker et al, 2013;Ongradi et al, 2019). Phylogenetic analysis of the fruit bat AdV-1 hexon shows it forms a clade separate from previously sequenced bat AdVs, and clusters with the HAdV clade with a high bootstrap value of 93 (Baker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The bat hexon shared 77% and 90% amino acid similarities with the HAdV counterpart across 58 and 63 amino acids, respectively, of the 900 amino acid hexon protein. The hexon gene of an isolated cat AdV presents with high sequence similarity to HAdV-1 as well (Ongradi, 1999;Ongradi et al, 2019). Independently, and geographically separated, the isolation of a cat AdV in a one-year old child hospitalized for acute gastroenteritis was reported in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, increasing evidence has shown that cats can be hosts of some human-infecting viruses. Ongradi et al ( Ongradi et al, 2019 ) first identified that cats can be animal hosts of human adenovirus 1. Zhao et al ( Zhao et al, 2019 ) reported that cats can be infected by human coronaviruses 229E (HCoV-229E) and (PDCoV) by serological screening, and they revealed the potential role of cats in the cross-species transmission of coronaviruses.…”
Section: Cross-species Of Coronaviruses Between Cats and Humans Or Ot...mentioning
confidence: 99%